The Effectiveness of Stress Management and Physical Activity to Working Stress Reduction on Nurses - Ismail Efendy; Miskah Afriany; Syarifuddin Lubis (Journal La Medihealtico, 2021)
From the first forty cases of working stress on workers, work stress incidence on nurses is located at the top of the list. The suitable handling and management for nurses are crucially required. Working stress management is a program to help someone overcome stress. The purpose of this research is to find out the effectiveness of stress management and physical activity towards working stress on nurses in TK II Putri Hijau Hospital. This research is using a quasi-experimental design with one group pretest-posttest design. The population in this research consists of 152 people and all of them are being examined using stress questionnaires to earn the stress level. Nurses who have medium stress level are chosen to be the samples of this research, which consist of 42 nurses that are being divided into 2 groups with 21 people in each group. Therefore, 21 people obtain stress management training treatment, and the other 21 people receive physical activity treatment. In this research, the Stress Scale (PSS-10) which is a self-report questionnaire is being used. Moreover, the data is processed using parametric analysis, which is Wilcoxon. Based on the research, it is found that stress management training and physical activity has a significant effect on the reduction of nurses working stress in TK II Putri Hijau Hospital Medan.